Sweet lime cultivation for increasing the productivity, profitability and sustainability - Basith, M A; Naik, M Ramesh; Ahire, L M (Indian Horticulture, 2021)
Sweet lime (Citrus limetta) popularly known as Mosambi is an important citrus fruit that has plenty of health benefits. The fruit is directly consumed as raw or more commonly in the form of juice. It is a rich source of vitamin C, helps in detoxification of body, boosts immunity, regulates digestion keeping the bowels healthy and prevents constipation. The juice is also rich in vitamin B complex and carotene which enhance the body immune system, improve eye sight and skin health. In India, it is grown in an area of 20.65 M hectares with a production of 33.15 M tons. The important states growing this crop are Andhra Pradesh, Maharashtra, Telangana, Madhya Pradesh, Punjab and Rajasthan. Andhra Pradesh ranks first in the area, production and productivity followed by Maharashtra, Telangana and Madhya Pradesh.